Which is More Effective: The Carrot or the Stick? Environmental Policy, Green Innovation and Enterprise Energy Efficiency–A Quasi-Natural Experiment From China - Wang, Yuan; Hu, Jiali; Hu, Yi; Wang, Yu (Frontiers in Environmental Science, 2022)
As the concept of carbon neutralization is valued, attention is paid to how environmental protection policies affect enterprises. However, little is known about how environmental policies affect enterprise energy utilization efficiency and green innovation. Based on Porter’s effectuation and deterrence theory, this paper proposes that an incentive environmental protection policy (environmental protection incentive) and punitive environmental protection policy (environmental protection regulation) have different impact mechanisms on enterprise green innovation and energy utilization efficiency. The following conclusions are drawn by using the data of listed enterprises since implementing the new environmental protection law in China and using the PSM-DID method to construct a quasi-natural experiment. 1) Environmental protection incentives are not conducive to improving energy utilization efficiency; 2) Environmental protection regulation can improve enterprise energy utilization efficiency; 3) Environmental protection incentives are not conducive to green innovation; 4) Environmental protection regulation is conducive to the green innovation of enterprises; 5) Green innovation plays a complete intermediary role in the relationship between environmental protection policies and enterprise energy utilization efficiency; 6) Different policies have heterogeneity on Enterprises: environmental protection incentives are conducive to the improvement of energy utilization efficiency of state-owned enterprises but not conducive to non-state-owned enterprises; The effect of environmental protection regulation on non-state-owned enterprises is more potent than that of state-owned enterprises. This study compares the impact of different environmental protection policies on enterprise green innovation and energy utilization efficiency and puts forward more effective and realistic targeted policy suggestions. This paper tries to understand the policy mechanism through comparison; The government has promoted green innovation and efficient and clean production by implementing policies for enterprises.